Thermodynamics and activity coefficients at infinite dilution for organic compounds in the ionic liquid 1-hexyl-3-methylimidazolium chloride. (January 2019) - Zhang, Miao; He, Zhuang-Zhuang; Kang, Rong-Xue; Ge, Ming-Lan
Graphical abstract: Highlights: Measurements of activity coefficients at infinite dilution using GLC. The (gas-liquid) partition coefficients were calculated. The excess thermodynamic functions, entropies, and Gibbs energies were calculated. The solubility parameter of the IL [HMIM][Cl] was determined. Selectivity and capacity for hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ). Abstract: The activity coefficients at infinite dilution, γ i ∞, for 33 solutes, including alkanes, cycloalkanes, alkenes, aromatic hydrocarbons, acetonitrile, acetone, tetrahydrofuran, ethyl acetate, 1, 4-dioxane, chloromethanes, alcohols in the ionic liquid 1-hexyl-3-methylimidazolium chloride, [HMIM][Cl], were determined by gas–liquid chromatography at temperatures range of (313.15–363.15) K. The gas-liquid partition coefficients, K L were calculated for all solutes. The densities of [HMIM][Cl] were measured at the temperature range from 313.15 K to 363.15 K. The values of the partial molar excess enthalpies at infinite dilution H - i E, ∞ were derived fromthe temperature dependence of the γ i ∞ values. The entropies T ref S - i E, ∞ and Gibbs energies G - i E, ∞ of organic solutes in [HMIM][Cl] at a reference temperature T ref = 298.15 K were also calculated from the γ i ∞ values. The Hildebrand's solubility parameters of the IL [HMIM][Cl] were also determined by the regular solution theory (RST) combined with Flory ''combinatorial'' equation. The values of selectivity and capacity for n -hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ) were calculated from γ i ∞ and compared to literature values for [HMIM]-based or [Cl]-based ILs for the same separation problems.